Landscape features causing the local congregation of honeybee males (Apismellifera L.). (10th May 2021) - Hayashi, Shinya; Satoh, Toshiyuki
Abstract: Aerial male congregation has been observed in eusocial Hymenoptera such as ants and bees. It is associated with mating and can help to minimize the frequency of inbreeding, which contributes to sustaining their society consisting of relatives. Male congregation often occurs at the same site each year. It has been suggested that there are factors defining the location for male congregation, but empirical evidence for this is currently scarce. In this study, landscape features for European honeybee male congregation areas, called drone congregation areas (DCAs), were evaluated by comparing DCA and non‐DCA landscapes as well as those of the entire surveyed study area using a digital elevation model, digital surface model, and land‐cover data. The observed DCAs were generally characterized as being open fields with few structures, having high levels of sun irradiance, and low elevation. The effective range of models that predicted the DCAs was smaller in the model with parameters considering objects above the terrain surface. The results provide an insight into the cues used by the bees to orientate and navigate themselves toward specific mating places, the mechanisms promoting the formation of local male congregations, and why certain locations are selected as mating places.